Proposal of combined therapeutic strategies for KRAS in non-small cell lung cancer based on an in silico analysis - Chapilliquen Ramírez, Daniela (2024)
Objective: Patients with non-small cell lung cancer positive for the anaplastic lymphoma kinase (ALK+) gene mutation who also have mutations in the Kirsten rat sarcoma (KRAS) gene, such as KRAS G12C, are showing resistance to both anaplastic lymphoma kinase (ALK) gene and KRAS inhibitors. Therefore, the interaction between ALK inhibitors and KRAS was analyzed to suggest a synergy between them. Materials and methods: The study performed homology modeling of the KRASwt, KRAS G12C and ALKwt structures. Subsequently, molecular dockings were carried out to determine the binding energy of ALK and KRAS inhibitors and to evaluate the possible interaction of ALK inhibitors with KRAS and the KRAS G12C structure. Finally, the expression in the RAS/MEK pathway was analyzed using the Western Blot technique. Results: The binding energy values show the potential interaction of ALKwt inhibitors, such as crizotinib and alectinib, with the KRASwt and KRAS G12C structures. The binding of crizotinib to KRASwt and KRAS G12C, respectively, indicates interaction energy values (42.77 kcal/mol and 46.20 kcal/mol) which are very similar to those obtained between crizotinib and ALK (42.37 kcal/mol). In turn, alectinib bound to the same site as drugs targeting KRAS and KRAS G12C, and showed interaction energy values (51.74 kcal/mol and 54.69 kcal/mol, respectively) higher than those obtained with ALK (44.94 kcal/mol). Finally, a significant decrease in RAS expression within the RAS/MEK pathway was observed in ALK+ and ALK 1196M lung cancer cell lines treated with crizotinib and alectinib. Conclusions: In silico techniques of this study demonstrate the potential binding of ALK inhibitors (crizotinib and alectinib) to the KRAS structure. In addition, this allows suggesting a possible combined therapy between KRAS and ALK inhibitors for cases of coexistence of both mutations that can be assessed in subsequent trials with cell lines.